Design of Standard Instrument Arrival (STAR) North Inbound at Kertajati International Airport - Evan Panangian Sianturi; Dwi Lestary; Elfi Amir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Kertajati International Airport is designed to serve as the main air gateway for West Java Province. However, there is currently no dedicated Standard Instrument Arrival (STAR) for flights arriving from the north. As a result, aircraft must follow indirect routes through several waypoints and different airspace sectors, leading to longer flight distances, increased workload for Air Traffic Controllers (ATCs), and reduced operational efficiency. This study aims to design an efficient and safe STAR North Inbound route for arrivals to Kertajati International Airport. The research adopts a Level 1 Research and Development (R&D) approach, consisting of literature review, data collection, flight procedure design based on ICAO Doc 8168 PANS-OPS, and design validation by certified Flight Procedure Designers. The results show that the proposed STAR North Inbound design reduces flight distance by 98.9 nautical miles compared to the current routing. Additionally, the new procedure minimizes airspace transitions and communication frequency changes, thereby reducing ATC workload and improving navigation service efficiency. From a safety perspective, the proposed design meets all obstacle clearance and protection area requirements in accordance with ICAO standards. In conclusion, the proposed STAR North Inbound route is deemed feasible for further review and development through inter-unit coordination, flight validation tests, and operational simulations prior to official implementation. The design supports safer, more effective, and more efficient air navigation services at Kertajati International Airport.